View Single Post
Old 2020-02-25, 08:21   #8
Nick's Avatar
Dec 2012
The Netherlands

67E16 Posts

Originally Posted by wildrabbitt View Post
Also, in case there's an obvious remedy to my latex not parsing properly, here's an example of what I wrote in the first post without the \\( and \\).

\sum_{n=1}^\infty \big(\frac{n}{q}\big)x^n=\frac{1}{1-x^q}\sum_{m=1}^{q-1}\big(\frac{m}{q}\big)x^m=\frac{xf(x)}{1-x^q}
LaTeX: just put backslash then open-square-bracket before it, and backslash then close-square-bracket afterwards:

\[\sum_{n=1}^\infty \big(\frac{n}{q}\big)x^n=\frac{1}{1-x^q}\sum_{m=1}^{q-1}\big(\frac{m}{q}\big)x^m=\frac{xf(x)}{1-x^q}\]
Nick is online now   Reply With Quote